Efficiency of the Use of Computer Memories and Execution Time in Structural Analysis - Hariandja, Binsar H. (President University, 2023)
The use of computer programming provides accurate and speedy analyses of structural systems. The accuracyand the speed of the analysis are due to the novelty of the computer, i.e., the speed in storing and retrieving large sizeof data, and the speed and the accuracy in the numerical computation. However, in old days, due to the limitedstorage capacities of old generations of the computers, and the use of limited main frame computers, used by somany parties, the efficient use of computer memory became an important issue. Moreover, the use of rented base ofcomputer time necessitated the efficient use of computer run time. The paper discusses the efforts to efficiently usethe computer memory and computer run times. These issues seem to remain important issues, even though to date,the tendency is to use of personal computers and laptops instead the use of rented main frame computers.